2015
DOI: 10.1016/j.clim.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Automated flow cytometric analysis across large numbers of samples and cell types

Abstract: Multi-parametric flow cytometry is a key technology for characterization of immune cell phenotypes. However, robust high-dimensional post-analytic strategies for automated data analysis in large numbers of donors are still lacking. Here, we report a computational pipeline, called FlowGM, which minimizes operator input, is insensitive to compensation settings, and can be adapted to different analytic panels. A Gaussian Mixture Model (GMM)-based approach was utilized for initial clustering, with the number of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 6 publications
2
19
0
1
Order By: Relevance
“…Unfortunately, expert manual gating has been shown to be particularly prone to inter-operator variability [7] and a tendency to overlook cell populations [810]. Recent efforts have developed new tools for high dimensional cytometry data that bring in elements of machine learning and statistical analysis, including clustering [1114], dimensionality reduction [8], variance maximization [15], mixture modeling [6, 1618], spectral clustering [19], neural networks [20], and density-based automated gating [21]. Here, we highlight use of these tools in a sequential single cell bioinformatics workflow (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, expert manual gating has been shown to be particularly prone to inter-operator variability [7] and a tendency to overlook cell populations [810]. Recent efforts have developed new tools for high dimensional cytometry data that bring in elements of machine learning and statistical analysis, including clustering [1114], dimensionality reduction [8], variance maximization [15], mixture modeling [6, 1618], spectral clustering [19], neural networks [20], and density-based automated gating [21]. Here, we highlight use of these tools in a sequential single cell bioinformatics workflow (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…[4,8] demonstrate the practical advantage of using the Gaussian mixture model relative to the traditional gating approach. It is shown that the performances of this automated approach can compete with manual expert analyses, and furthermore has the added benefits of speed, objectivity, reproducibility, and the ability to evaluate several subpopulations in many dimensions simultaneously [9]. The mixture model approach was recently improved in order to deal with large data sets and compared with the top-ranked approaches [1].…”
Section: Comparison With Other Approachesmentioning
confidence: 99%
“…Methods such as flowMeans (25), flowMerge (26), or FLOCK (27) identify cell populations in FCM data by means of unsupervised hard clustering. In the context of automated FCM analysis, Gaussian Mixture Models (GMMs) have been successfully applied (23,26,(29)(30)(31). In the context of automated FCM analysis, Gaussian Mixture Models (GMMs) have been successfully applied (23,26,(29)(30)(31).…”
mentioning
confidence: 99%
“…In the context of automated FCM analysis, Gaussian Mixture Models (GMMs) have been successfully applied (23,26,(29)(30)(31). There are only a few supervised approaches for automated FCM analysis (30,(32)(33)(34). There are only a few supervised approaches for automated FCM analysis (30,(32)(33)(34).…”
mentioning
confidence: 99%
See 1 more Smart Citation